Studi profitabilitas Bank Muamalat berbasis rasio Net Profit Margin (NPM) pada masa pemulihan ekonomi 2020–2024 - akbar, moh rafi; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the profitability performance of Bank Muamalat Indonesia using the Net Profit Margin (NPM) ratio during the 2020–2024 period. Net Profit Margin is a financial ratio that measures the bank’s ability to generate net profit from its operational revenue. The fluctuation of profitability serves as an important indicator in evaluating how effectively the management controls operational expenses and optimizes income. This research applies a descriptive quantitative approach utilizing the annual financial reports of Bank Muamalat as the primary data source. The findings show that the NPM value experienced considerable instability throughout the study period. In 2020 and 2021, the NPM value remained below 1%, indicating high operational costs relative to revenue. The year 2022 marked a significant improvement with the highest NPM achievement of 5.55%, showing strong efficiency and profitability. However, the value sharply declined again to 0.84% in 2023 before slightly improving to 1.36% in 2024. Overall, Bank Muamalat’s profitability still requires further enhancement to achieve sustainable and consistent performance. This study highlights the importance of strengthening income-generating activities and implementing better operational cost management to improve future financial performance..